Study on Potential and Feasibility of Lemon Myrtle as Biomass Waste in Biochar Production - Hafriz R.S.R.M.; Habib H.S.; Isa M.R.; Samsudin A.H. (American Institute of Physics, 2025)
The rapid waste generation from forestry, agriculture, and industry is one of the world?s critical challenges contributing to socio-economic and environmental challenges. Specifically, exponential population growth, economic development, and rapid urbanization are the key contributors to waste accumulation, which also causes severe ecological problems involving air and water pollution. By utilizing these wastes, there would be a significant cost reduction in the raw material costs. Malaysia Agriculture Research and Development Institute (MARDI) has introduced a new industrial crop, Lemon Myrtle, originating from Queensland, Australia. The essential oil extracted from this crop possesses many benefits as the citrus content is the highest compared to other citrus-containing crops. As for the economic benefits of Lemon Myrtle, it is concluded by MARDI to be more profitable than palm oil. However, no study has been done on the potential of Lemon Myrtle biomass waste as a renewable energy source of feedstock. Thus, managing this waste and upcycling it into valuable products such as solid biochar, liquid biofuel, and gas fuel can create a circular economy in the pipeline between the commercial and industrial sectors while contributing to carbon reduction. In this study, the characterization of different biomass via proximate, ultimate, and thermogravimetric analysis has been carried out. Approximate and ultimate analysis, lemon myrtle possesses highly volatile matter and fixed carbon with less ash and moisture suitable for biochar production as a feedstock. At the same time, thermogravimetric analysis of different parts of lemon myrtle used determined the degradation of biomass composition, such as cellulose, hemicellulose, and lignin. ? 2024 American Institute of Physics Inc.. All rights reserved.